Factors influencing migration of Metapenaeus dobsoni (Miers, 1878) in the Negombo Lagoon - Jayawardane, P A A T; Gunawardane, M G K (Indian Journal of Fisheries, 2011)
The factors influencing migration of M. dobsoni in the Negombo lagoon, SriLanka are presented. Juveniles of M. dobsoni occur in the Negombo lagoon andon maturing they return to the sea off Negombo for reproduction. The cohortanalysis indicated two pulses of immigration to the nursery areas in Februaryand June. The estimated growth rates for juveniles were relatively high comparedto that of adults. Three groups of shrimps were identified in the lagoon :small quick movers, larger long stay ones and an intermediate group. Emigrationis not restricted to maturing juveniles but occurs across all the ages. Therewere few identifiable emigration pulses from lagoon towards the off shore areas.It appears that the resultant osmotic stress due to low saline waters in thelagoon during the periods with high precipitation levels may be the strongestinfluence triggering the onset of emigration of shrimps.